Expedition Oe: A Visual-Storytelling Map on Rote Island’s Lakes - Dany Laksono (Jurnal Geospasial Indonesia, 2019)
Rote Island has long been known as a tourism destination, especially for its beaches and small islands which are well known surfing spots. However, many other aspects of Rote Island, such as its inland waters, left unexplored and are unknown to tourists or stakeholders. The lack of infrastructure is one of the factors causing underdevelopment in these area. This paper reports the outcome of an expedition set to uncover the uniqueness of Rote Island’s tourism potential, especially on its inland waters. The expedition involves researcher from some of Indonesian institutions related to inland waters, such as LAPAN, LIPI, PUPERA, KLHK and KKP to conduct some preliminary research on Rote Island’s saltwater lake. Mobile devices equipped with GIS software were used to obtain data during the survey. Some of the findings including the misleading toponyms found in online sources of the lakes, the biogeophysical condition of the lakes, as well as vegetations and wildlife of the area. The Rote Island Snake-necked Turtle (Chelodina Mccordi) is one of the near-extinct species which habitat needs to be identified and well-preserved, thus tourism should take into account natural preservation in the lakes and its surroundings. Based on the results we suggest that a Geopark should be initialized in and around Rote Island’s lakes. These findings are presented as a storytelling map, both to attract tourism and to emphasize the geospatial aspects of the lakes. A WebGIS is also developed to integrate data from different institutions to aide decision making. The result is geopark4rote.com, which present the storytelling map and WebGIS to be used by tourist and decision makers alike to explore the richness of Rote Island through geospatial data.